Overcoming Bilateral Disputes as Part of the EU Accession Process - Vasko Naumovski (European Studies Department, Faculty of Philosophy at Sofia University “St. Kliment Ohridski”, 2019)
Bilateral disputes have presented a significant obstacle for EU enlargement, especially in the region of South-Eastern Europe. The disputes between Slovenia and Croatia, Macedonia and Greece, Turkey and Greece/Cyprus - demonstrated the need for a more cohesive approach in order to avoid situations where bilateral issues could pose a threat to the enlargement policy. Moreover, future enlargement rounds may be endangered by additional disputes - Croatia and Serbia, Serbia and Kosovo, Albania and Serbia, etc. Historic, cultural and political issues often favor national interests, while the common European interest remains neglected. The idea for a “Europe whole, free and at peace” can be realized only with the necessary political will and courage, strong determination for completion of the European project, and continuous commitment to the process that has brought benefits to millions of European - enlargement. Instead of maintaining the fear of “importing conflicts”, EU is the most appropriate actor that can contribute to solve them, using all the tools available in the accession process. Lessons learned, existing challenges, as well as potential outcomes are analyzed in this paper.
Keywords: European Union, EU Enlargement, Western Balkans, Bilateral Disputes